Performance Enhancement of an Air-Conditioning System using a Passive Add-on Device. (September 2020) - Nguyen, V.; Mehri, R.; Godbout, G.; Matida, E.
Highlights: The performance of an air-conditioning unit with an add-on device was investigated. The add-on was found to reduce the radial velocity, hence streamlining the flow. An overall performance enhancement of 5.4% was found when using the add-on device. Abstract: Performance measurements of an air-conditioning system was performed with and without a Passive Add-on Device installed on top of its condenser unit. This device has a cylindrical shape with fixed radial blades, combining characteristics that streamline the flow, while changing its rotational speed. In addition to the thermodynamic measurements, the flow velocity distributions at the outlet of the condenser fan unit (no Add-on Device case) as well as at the outlet of the Add-on Device were both measured using hot-wire anemometry. The Add-on Device increased flow rotation as well as uniformity of axial velocity, while reducing the radial velocity component. By streamlining the flow, the Add-on Device led to enhancements by 5.4% in terms of overall coefficient of performance of the tested air-conditioning unit, within the range of tests conducted in the present work.